Financialization of the economy, business, and household inequality in the United States - Mettenheim, Kurt von, 1957- author.
1 online resource.
Keywords: "This volume on the political and social economy of financialization in the US focuses on the unexpected consequences of the rise of finance for the American macroeconomy, the financialization of household inequality, and the hollowing out of nonfinancial business enterprises. A historical-institutional balance-sheet approach to long term trends and recent changes reveals serious anomalies and provisos for critical, heterodox, and mainstream economic theories and provides new perspectives on debates about political economic change in advanced economies since the 2007-2008 financial crisis. This book marks a significant contribution to the literature on financialization and studies in social economics, household economics, the changing structure and management of nonfinancial business enterprises, and American political economy. Kurt Mettenheim taught at the FGV-EAESP in São Paulo, Brazil, Oxford University, the University of Pittsburgh, and Columbia University. Olivier Butzbach is a Senior Researcher in Political Economy at the Department of Political Science of the University of Campania 'Luigi Vanvitelli', Italy"--